Extraction of Cellulose from Sugarcane Bagasse Optimization and Characterization - Getu T. Melesse; Fekadu G. Hone; Mulualem A. Mekonnen (Advances in Materials Science and Engineering)
In this study, cellulose was extracted from sugarcane bagasse (SCB) through a convenient five-step treatment, and procedures were performed. During the alkaline curing process of the extraction of cellulose, NaOH has a concentration of (0.5, 1.5, 2.75, and 4%) and the extraction time (15, 30, and 45 min) at a constant temperature of 120°C were taken as variables and perfectly optimized by response surface methodology (RSM) for cellulose with the highest product. The optimum conditions were found to be 2.75% NaOH, 120°C, and 45 min with a cellulose yield of 73.71 ± 0.67% cellulose, 17.22 ± 0.82% hemicellulose, and 9.07 ± 0.95% lignin. Though most of the lignin was eliminated during the alkaline and dilute acid pretreatment process, the remaining lignin was removed by a solution treatment of 4% NaOH, and 21.92% H2O2 at 121°C for 44.97 min where the cellulose yield was found as 89.75 ± 0.64%, hemicellulose was 6.15 ± 0.83%, and lignin was 2.65 ± 0.66%. Morphological analysis revealed that the average diameter of the cellulose was 12.06 µm. Thermal and XRD diffraction analysis showed that the cellulose is thermally stable and has a crystallinity index of 31.63%. FTIR spectra demonstrate that cellulose was successfully extracted due to the removal of noncellulose components.